(untitled) (ASEAN Engineering Journal, 2025)
This study presents a dual-band rectifier that operates at 2.4 GHz and 5 GHz frequency bands with high peak PCE and wide dynamic range performance. The proposed design utilized a cross-coupled rectifier architecture with bulk-biasing. An L-matching network was inserted between the source port and the rectifier for maximum power transfer. A peak PCE of 74.93 % at -11 dBm input power was achieved at 2.4 GHz operating frequency. On the other hand, a peak PCE of 72.75 % at -11 dBm input power was achieved at 5 GHz operating frequency with a fixed 30 KΩ load. The design was optimized and offered a broad dynamic range of 12.74 dB and 10.28 dB for the 2.4 GHz and 5 GHz mode, respectively. The Vout measured for the 2.4 GHz was 1.05 V with -9 dBm input power, while for the 5 GHz, the Vout measured was 1.04 V at -4 dBm input power. The system was able to achieve 1 V at a sensitivity of -12.35 dBm and -11.52 dBm, for 2.4 GHz and 5 GHz respectively. Overall system integration at -1 dBm input power, the voltage output of the rectifier measured 1.47 V. On the other hand, the LDO measured a constant 1.2 V voltage output. The design was implemented in 65 nm CMOS process Technology.